The Transatlantic Trade and Investment Partnership (TTIP) in the Kronen Zeitung. (December 2017) - Kopf, Susanne
Highlights: The Kronen Zeitung draws on a nationalist discourse to motivate action against the TTIP. The TTIP is a threat to Austrian food security and, generally, to the Austrian Heimat ('homeland'). The TTIP is represented as immoral and the TTIP's effects as unnatural. In contrast, the opposition against the TTIP is a powerful and biblically just civic movement. Abstract: The Transatlantic Trade and Investment Partnership (TTIP) aims at levelling the commercial playing field between the European Union and the United States of America by, e.g., lowering tariffs to promote trade between the two economies. However, since early 2014, that is, even before the treaty negotiations could lead to concrete output, the free trade agreement has been faced with protests from both sides of the Atlantic and from individuals/groups from various ideological backgrounds. This paper draws on a corpus-assisted approach to examine how the TTIP is reported on in the Austrian newspaper Kronen Zeitung (Krone). Among other reasons, the newspaper was chosen as a source of data due to its clout as "the most widely read paper in the advanced industrialized world" "[i]n terms of readership per capita […] (Art, 2006). Indeed, the newspaper's influence has remained steady at a readership of 40 to 47% (Meyer & Rosenberger, 2015). The corpus examination has found that the newspaper predominantly employs a nationalist discourse in order to elicit its readership's rejection of the TTIP. Apart from cultivating resistance against this trade agreement, the newspaper's reporting on the TTIP might affect its readership in (further) honing and normalising nationalist attitudes and general opposition against international cooperation. Moreover, the Krone might attract hitherto unreached segments of the Austrian population who, opposing the TTIP, are willing to join the Krone 's counter-TTIP campaign and are then vulnerable to subscribing to the newspaper's more general discursive choices .